Drem Team Slagelse; historik og kommunalpolitik - Lundberg, Rune (Forum for Idræt, 2007)
Artiklen sætter fokus på historikken og spørgsmålet om, hvorfor Anja Andersens Dream Team blev placeret i Slagelse, samt hvilken betydning holdet har haft for byen. Rune Lundberg: DreamTeam in Slagelse – history and municipal politics In the fall of 2006 Anja Andersen proclaimed, that by the end of 2007 she would leave her position as coach for the, at that time, best women’s handball team in the World – the Slagelse Dream Team. In a period of less than 6 years she had turned a second division handball team into one of the worlds most successful. An era was about to end, but what impact had the Dream Team had on the city of Slagelse? What imprints did she leave behind and how would the club, the municipality and the local community handle her absence? The Museum of Southwest Zealand set out to investigate and document the last 6 years with Slagelse Dream Team, as it poses a very important period of modern day history in the Region. The article focuses on the circumstances that led to the funding of an elite handball team in Slagelse and how this has affected the community on a political level.